Seeing vs Experiencing: Generation Z’s Needs and Satisfaction in Consuming 2D vs VR News - Citraningtyas, Clara Evi Candrayuli; Utami, Isti P. T.; Budiharjo, Slamet (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2025)
This study aims to examine the comparative experience of Generation Z as potential news consumers when utilizing two-dimensional (2D) and virtual reality (VR) news sources. What are their needs, and if those needs are fulfilled. Participants in the study were students between the ages of 18 and 21 who were enrolled in one of ten different study programs and lived in urban regions of Jabodetabek Indonesia. The study makes use of the concept of Gratification Sought, which encompasses five different aspects of needs: cognitive, affective, personal identity/interactive needs, social interaction and integration, and tension relief. The study employs a mixed-method approach, and the data gathering procedure is carried out through the use of questionnaires. A number of conclusions concerning the needs and levels of satisfaction related with the consumption of 2D and VR news can be identified from the outcomes of the study. Virtual reality media succeeds in fulfilling affective needs and delivering higher levels of satisfaction on identity and social connection when compared to 2D media. Nonetheless, there are limitations in adequately addressing cognitive needs. Meanwhile, 2D media remains a robust option for informational and cognitive needs, but it has a tendency to inadequately address affective needs and managing tension. ABSTRAK Penelitian ini bertujuan untuk mengkaji pengalaman komparatif Generasi Z sebagai calon konsumen berita saat menggunakan sumber berita dua dimensi (2D) dan realitas virtual (VR). Penelitian ini mengeksplorasi apa kebutuhan mereka dalam mengkonsumsi berita dan sejauh mana kebutuhan tersebut terpenuhi. Informan dalam penelitian ini adalah mahasiswa berusia 18 hingga 21 tahun yang terdaftar dalam salah satu dari sepuluh program studi dan tinggal di wilayah perkotaan Jabodetabek di Indonesia. Penelitian ini mengadopsi konsep Gratification Sought yang mencakup lima aspek kebutuhan: kognitif, afektif, identitas pribadi/kebutuhan interaktif, interaksi dan integrasi sosial, serta pelepasan ketegangan. Pendekatan yang digunakan adalah metode campuran, dengan pengumpulan data melalui kuesioner. Hasil penelitian mengungkap sejumlah temuan terkait kebutuhan dan tingkat kepuasan yang berkaitan dengan konsumsi berita 2D dan VR. Media VR terbukti lebih mampu memenuhi kebutuhan afektif serta memberikan tingkat kepuasan yang lebih tinggi dalam aspek identitas dan koneksi sosial dibandingkan dengan media 2D. Namun, media VR memiliki keterbatasan dalam memenuhi kebutuhan kognitif secara memadai. Di sisi lain, media 2D tetap menjadi pilihan yang kuat untuk memenuhi kebutuhan informasi dan kognitif, meskipun cenderung kurang optimal dalam mengakomodasi kebutuhan afektif dan pengelolaan ketegangan..